Scouse Dialect in English and Tabulahan Dialect in Mamuju Language: A Dialectology Study - Arta Desiyana; Sudirman Maca; Andi Tenri Abeng (Fakultas Sastra, Universitas Bosowa, 2022)
This research aims to look at language variations that occur phonologically and lexically in the Scouse dialect or Liverpool English in English and Tabulahan dialect in Mamuju language. Sources of the data for the Tabulahan dialect and Mamuju language were obtained directly from the informants as native speakers of the Tabulahan and Mamuju languages. Meanwhile, the Scouse dialect and English data as a comparison were obtained from previous research conducted by Honeybone (2007) and Baranova (2015). The writer used a qualitative method through a dialectological approach and contrastive analysis. The results of this study show that there are similarities and differences. Phonologically, similarities occur in the features of Vocal Change and Lenition. The difference occurs in the features of the TH-stopping and the category of Rhotic and non-Rhotic which the Tabulahan Dialect does not have this feature but is found in the Scouse Dialect in English. Lexically, both dialects have variations in word classes such as nouns, verbs, adverbs, and adjectives. While the differences occur in other word class variations such as pronouns, prepositions, determinants, conjunctions, numbers and question words which are only found in the Tabuhanan dialect.